A new software development paradigm for intelligent information systems. (26th August 2020) - Dehraj, Pooja; Sharma, Arun
The continuous growth in software management cost requires the development of self-managed software systems. Using self-managed property, a system will take intelligent decisions to make a system work properly. Autonomic computing is the technique, which is used to develop such systems. Autonomic computing systems are highly reliable software systems. To enhance the quality of software systems, implementation of autonomic computing-based software development life cycle process may be a novel idea. It involves autonomous decision making by the autonomic component during the development of software. This approach reduces the complexity of the software development process. In addition, it resolves the purpose of autonomic computing to reduce software complexity and do real-time exception handling. In this paper, the implementation of the autonomic advisor-based software development process is proposed using the cloud computing technique. Cloud computing helps the developers to develop software, applications using deliverable services such as platform, infrastructure, and software. During the implementation and usage of autonomic advisor, the database becomes heavier. Therefore, to resolve such issues, cloud computing will be a beneficiary step. Other benefits of such an autonomous software development life cycle process are discussed further in this paper.